2015
DOI: 10.11648/j.sjph.20150302.13
|View full text |Cite
|
Sign up to set email alerts
|

Critical Segments in the Dissemination and Transmission of Salmonella Species from Poultry Production in Calabar, Nigeria

Abstract: Salmonella species are ubiquitous enteric bacteria, its ability to survive at different stages of the poultry production and food processing chain has been frequently reported in recent years. The present study was undertaken to investigate the points in the segments involved in the production of poultry in Calabar as vital sources of dissemination and transmission of Salmonella species to humans. A total of 374 samples were collected from three study segments involved in the production of poultry in Calabar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…The isolation rate of Salmonella spp. obtained in this study was lower compared with the result of Yhiler & Bassey (2015), who reported an isolation rate of 59.1% of Salmonella spp. from cloacal swab of poultry in Calabar Cross River state, Nigeria.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The isolation rate of Salmonella spp. obtained in this study was lower compared with the result of Yhiler & Bassey (2015), who reported an isolation rate of 59.1% of Salmonella spp. from cloacal swab of poultry in Calabar Cross River state, Nigeria.…”
Section: Discussioncontrasting
confidence: 94%
“…in broilers at Ibague, Colombia, and of Al-Khayat & Khammas (2016) who reported a prevalence of 10.4% of Salmonella from layers and broilers in Baghdad. However, Yhiler & Bassey (2015) reported an isolation rate of 59.1% of Salmonella from poultry in Calabar, Nigeria. The isolation rate of Salmonella spp.…”
Section: Discussionmentioning
confidence: 98%